DRY TAP: A DIAGNOSTIC ALERT FOR UNDERLYING BONE MARROW PATHOLOGY - Ahmad, Saqib Qayyum; Yusuf, Rizwan; Zafar, Nadeem; Ali, Nadir (Journal of Ayub Medical College Abbottabad, 2015)
Background: Dry tap is an annoying experience in bone marrow (BM) findings, especially in cases where the diagnosis may hinge on BM findings. This study was conducted to determine, on the basis of bone marrow (BM) trephine biopsy, the frequency of various underlying conditions causing a dry tap, among different age groups. Methods: It was a descriptive study carried out at PAF hospital Mianwali, Pakistan from 1st Jan 2009 to 31 Dec 2012. Record of all BM aspirations and trephine biopsies performed during 4 years was retrieved from hospital's laboratory. Total number of BM aspirations and trephines were counted and the subject's ages and genders recorded. Frequencies and percentages of patients with dry tap, in paediatric group (<15 years of age), young to middle-aged group (15-59 years) and the elderly (‰¥60 years) were calculated. Diagnoses of patients with dry tap made on BM biopsy were noted for each group and their frequencies calculated. Results: Of 548 BM aspirations, dry tap was encountered in 52 (9.5%) cases. Acute lymphoblastic leukaemia (ALL) was the commonest cause of dry tap in paediatric age, seen in 6 (60%) of 10 children. In young to middle-aged group, non-Hodgkin lymphoma (NHL) was the commonest cause, found in 6 (30%) of 20 cases. NHL and metastatic tumours, seen in 8 (36.4%) and 6 (27.3%) of 22 patients respectively, were the most frequent causes of dry tap in the elderly. Conclusion: Dry tap, in most of the cases, is like a diagnostic alert for the presence of an underlying BM pathology, nature of which depends upon age group. Keywords: Bone marrow examination, biopsy, needle biopsy, lymphoma